IMPLIKASI PROGRAM PARENTING TERHADAP PENDIDIKAN KARAKTER ANAK - Murdiani, Ni Ketut (JURNAL YOGA DAN KESEHATAN, 2019)
Education is a lifelong learning process that can be characterized by changes in behavior. The learning process in the learner and the results obtained are the ability to adjust to the environment and fulfillment of needs. Education can be held on formal, informal and non-formal channels. This form of education does not seem to be able to make character of the students. Formal education tends to emphasize cognitive aspects only. While informal and non-formal education is not able to provide an example to children so that they are not optimally developed psychologically. Especially education obtained from parents. Here the cause may lie in the lack of knowledge of parents about how to educate children well. On this basis it is very important that there is a parenting program in elementary schools. With the parenting program, parents will be able to educate and care for chil- dren properly and correctly so that children can become noble characters. This parenting program usually affects parents in their knowledge of how to educate properly, and has a great influence on the character of the child.